KEKERASAN DALAM RUMAH TANGGA (KDRT) TERHADAP ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA (HAM) - SRYANI BR. GINTING; CHRISTINA NM., TOBING (LP2MTBM MAKARIOZ, 2023)
Human rights in the perspective of the Indonesian Constitution have the spirit of Pancasila. Indonesia as a constitutional state implements the principles of the